Analisis Korelasi Karakteristik Skrining Dengan Kejadian Tuberkulosis Paru Pada Anak - Dovi Dwi Mardiyah Ningsih; Retno Dewi Prisusanti (Proceeding of the International Conference on Health Sciences and Nursing, 2024)
Pulmonary tuberculosis (TB) is one of the main causes of morbidity and mortality in children, especially in developing countries. Screening is an important first step to detect cases early. Pulmonary tuberculosis is a chronic infectious disease that is a problem not only in Japan but also throughout the world. Screening characteristics that influence the incidence of pulmonary tuberculosis include house ventilation, population density, type of house floor, diet, exclusive breastfeeding, low birth weight, BCG vaccination, smoking status and location, and contact with sick people. The aim of this study was to determine the relationship between screening characteristics and the incidence of pulmonary TB in children at the Dau Community Health Center in 2019. This research was conducted using a cross-sectional approach with a total of 78 participants. The results of the study showed that there was a significant relationship between screening characteristics and the incidence of pulmonary TB in children. The researchers suggest integrated collaboration between nutrition, HIA and immunization programs, along with TB elimination programs in community health centers.